Gun Control in the Crosshairs: Christian Nationalism and Opposition to Stricter Gun Laws. (21st July 2018) - Whitehead, Andrew L.; Schnabel, Landon; Perry, Samuel L.
Despite increasingly frequent mass shootings and a growing dissatisfaction with current gun laws, American opposition to federal gun legislation remains strong. The authors show that opposition to stricter gun control is closely linked to Christian nationalism, a religious cultural framework that mandates a symbiotic relationship between Christianity and civil society. Using data from a national population-based survey, the authors show that Christian nationalism is an exceptionally strong predictor of opposition to the federal government's enacting stricter gun laws. Of all the variables considered, only general political orientation has more predictive power than Christian nationalism. The authors propose that the gun control debate is complicated by deeply held moral and religious schemas that discussions focused solely on rational public safety calculations do not sufficiently address. For the substantial proportion of American society who are Christian nationalists, gun rights are God given and sacred. Consequently, attempts to reform existing gun laws must attend to the deeper cultural and religious identities that undergird Americans' beliefs about gun control.